Genome size determination of Eclipta alba and Aloe barbadensis (Bangladesh Journal of Pharmacology, 2015)
There is abundant genetic diversity of pharmacologically important plants around the globe and this pool of genetic variation serves as the base for selection as well as for plant improvement. The major cause of such genetic diversity is the variation in their genetic material, as called genome. In the present study, an attempt was made to determine the genome size of Eclipta alba and Aloe barbadensis by flow cytometry using Pisum sativum as a reference standard. The nuclear DNA was calculated as 8.7 pg for E. alba and 9.0 pg for A. barbadensis. The genome size of E. alba and A. barbadensis was estimated to be 4.27 x 109 bp and 4.42 x 109 bp, respectively. Information on genome size and DNA content of these two pharmacologically important plants would provide a useful tool for future molecular biological investigations.